A Hybrid Framework for Guidance and Counseling in Indonesia: Integrating ASCA and ABKIN for Teacher Competence Development - Rusmana, Nandang; Hafina, Anne; Yustiana, Yusi Riksa; Kurniati, Euis; Azzahrah, Humairah; Diba, Salsabila Farah (KONSELOR, 2024)
This study aims to develop a comprehensive school guidance and counseling program model by integrating the international models of ASCA (American School Counselor Association) and ABKIN (Indonesian Guidance and Counseling Association), tailored to the local context of Indonesia. The research utilised the Borg and Gall research and development design, which includes development, testing, and validation steps. A purposive sample of 141 guidance and counseling teachers from various educational levels across Indonesia participated in the study. The developed model consists of two main frameworks: a general framework and a specific framework. The general framework includes the foundation, delivery system, management, and accountability, while the particular framework covers the rationale, philosophy, vision and mission, and program audit. The model was validated by four expert validators: (1) a professor of Guidance and Counseling from Semarang State University, focusing on junior high school education; (2) a professor from Malang State University, focusing on senior high school education; (3) a professor from Indonesian Education University, focusing on elementary school education; and (4) an expert lecturer in Early Childhood Education (PAUD). The validation results showed an average score of 4.1 out of 5, indicating that the model was considered satisfactory in feasibility and completeness. Suggested improvements emphasised further adaptation to local conditions and strengthening evidence-based accountability. This model is expected to enhance the effectiveness of school counseling services by supporting student development in three main domains: the academic domain (learning to learn), the career/vocational domain (learning to earn), and the personal/social domain (learning to live). With a more adaptive approach to the specific needs at various educational levels, this guidance and counseling model can better support student growth.